Molecular Markers Distinguishing T Cell Subtypes With TSDR Strand-Bias Methylation - Minskaia, Ekaterina; Saraiva, Barbara C.; Soares, Maria M. V.; Azevedo, Rita I.; Ribeiro, Ruy M.; Kumar, Saumya D.; Vieira, Ana I. S.; Lacerda, João F. (Frontiers in Immunology, 2018)
Human regulatory CD4+CD25+FOXP3+ T cells (Treg) play important roles in the maintenance of self-tolerance and immune homeostasis in various disease settings and are also involved in the suppression of effective immune responses. These cells are heterogeneous in phenotype and function and the ability to reliably distinguish between various FOXP3-expressing subpopulations can affect the development of successful therapies. This study demonstrates that hypomethylated CpG sites, present in four regions of the FOXP3 locus, CAMTA1 and FUT7 gene regions, can be used to distinguish various subsets of T lymphocytes in donors of both genders. Previously unreported strand-bias hemimethylation pattern within human FOXP3 promoter and TSDR in some donors of both genders is also uncovered, with coding strand being demethylated within promoter and methylated within TSDR in all T lymphocyte subtypes. Methylation of the template strand follows the previously described pattern with both regions being more demethylated in Treg subtypes and mostly methylated in Tcon. The strand-specific approach may prove to be instrumental in correctly defining FOXP3-expressing subsets when using FOXP3 TSDR as prognostic marker in health and disease.